HEMOGLOBIN VALUE OF ETAWA CROSSBREED SUFFERING FROM SUBCLINICAL MASTITIS IN RAKA ETAWA FARM, SINGAPADU KALER GIANYAR BALI - Kero, Christine Ratu Azalia; Kendran, Anak Agung Sagung; Mufa, Romy Muhammad Dary; Siswanto,; Sukada, I Made; Jayanti, Putu Devi (Buletin Veteriner Udayana, 2024)
One of the health problems that occurs in Etawa crossbreed (PE) goat farms as dairy goats is subclinical mastitis. Subclinical mastitis is potential mastitis that does not show clinical symptoms in the udder. In an effort to support the health of PE goats as dairy livestock, it is necessary to carry out routine health checks, one of which is blood tests such as hemoglobin tests. This study aims to determine the hemoglobin value of Etawa crossbreed goats (PE) suffering from subclinical mastitis. Blood samples were taken after the CMT test on goats that were positive for subclinical mastitis. After that, a blood sample was taken from the jugular vein area using needle blood colection with the help of vacuntainer holder and put in coolbox. The blood samples that have been taken are then examined using a Hematology Analyzer RT 7600. The data obtained is then analyzed descriptively regarding hemoglobin values. The research results showed that hemoglobin in PE goats showed values ​​within the normal range, namely 8.46 ± 0.85 g/dL with a range of 7.4 – 9.6 g/dL. To support better results, farmers need to maintain the health of their livestock by routinely carrying out livestock checks, including blood tests.